2017
DOI: 10.1152/japplphysiol.00436.2017
|View full text |Cite
|
Sign up to set email alerts
|

Glucose transport across lagomorph jejunum epithelium is modulated by AMP-activated protein kinase under hypoxia

Abstract: The gastrointestinal epithelium possesses adaptation mechanisms to cope with huge variations in blood flow and subsequently oxygenation. Since sufficient energy supply is crucial under hypoxic conditions, glucose uptake especially must be regulated by these adaptation mechanisms. Therefore, we investigated glucose transport under hypoxic conditions. Jejunal epithelia of rabbits were incubated in Ussing chambers under short-circuit current conditions. Hypoxia was simulated by gassing with 1% O instead of 100% O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 51 publications
(51 reference statements)
3
16
0
Order By: Relevance
“…Kles and Tappenden [7] reported that the transepithelial transport of glucose was impaired under hypoxia, while glutamine transport was not. In accordance with that, it has been shown that the activity of the sodium-coupled glucose transporter SGLT1 was diminished under hypoxia in jejunum epithelium [5,8,9]. This downregulation appears to be a targeted and reasoned adaptation rather than a sign of cellular failure.…”
Section: Introductionsupporting
confidence: 62%
See 3 more Smart Citations
“…Kles and Tappenden [7] reported that the transepithelial transport of glucose was impaired under hypoxia, while glutamine transport was not. In accordance with that, it has been shown that the activity of the sodium-coupled glucose transporter SGLT1 was diminished under hypoxia in jejunum epithelium [5,8,9]. This downregulation appears to be a targeted and reasoned adaptation rather than a sign of cellular failure.…”
Section: Introductionsupporting
confidence: 62%
“…However, for the epithelium’s survival under challenging circumstances such as a sudden onset of hypoxia, an adaptation within minutes is necessary. Recent research provided evidence for a fast adaptation to hypoxia taking place on the protein rather than on the gene expression level [5,6]. This quick reaction might at least bridge the critical time until HIF-mediated adaptation mechanisms are set to work and could, thus, be a critical point for early therapeutic intervention.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An activation of AMPK under hypoxia has been demonstrated in various tissues and cell types, ranging from brain [32][33][34], liver [35] and skeletal muscle [36][37][38] to cardiomyocytes [39,40], alveolar epithelial cells [41,42], intestinal epithelial cells [43,44] and fibroblasts [45]. Interestingly, an inhibition of AMPK activation under hypoxia was reported after long-term hypoxia (in this case 8% oxygen for 12 d) [46].…”
Section: The Role Of Ampk Under Hypoxiamentioning
confidence: 93%